Permanence risks limit blue carbon financing strategies to safeguard Southeast Asian mangroves - Valerie Kwan; Daniel A. Friess; Tasya Vadya Sarira; Yiwen Zeng (Communications Earth & Environment)
Abstract Conserving Southeast Asia’s mangroves is a vital natural climate solution, and their protection could be supported by blue carbon credits. However, such financing strategies expose conservation efforts to socioeconomic and climate change permanence risks. Here, we evaluate the potential impacts of permanence risks on the ability of blue carbon financing to safeguard mangroves. Using opportunity costs associated with oil palm, rice and aquaculture land use conversion as indicators of socioeconomic risks, and predicted cyclones and sea-level rise as indicators of climate change risks, we find that 85% of mangroves are likely to experience some form of permanence risk. Diverse funding sources and risk mitigation measures need to be contextualised in a long time horizon to maintain conservation viability into the future. Understanding how these risks interact and affect mangrove conservation efforts over timescales relevant to carbon permanence is key to minimizing risks and ensuring positive socio-ecological outcomes.